SEIZURE PROPHYLAXIS IN GLIOMA - UK NEUROSURGICAL SURVEY AND CLINICAL TRIAL. (3rd October 2018) - Jenkinson, Michael; Watts, Colin; Vale, Luke; Marson, Anthony; Bulbeck, Helen; Grant, Robin
Abstract: INTRODUCTION: There is no consensus regarding the utility of prophylactic anti-Epileptic Drugs (AED) given to patients with supratentorial glioma before surgery, who have not had seizures. Newer AEDs have fewer adverse effects but their efficacy in preventing new onset seizures remains to be proven. In 2016, we surveyed all members of the Society of British Neurosurgeons (SBNS) to determine current practice and establish whether a randomised controlled trial (RCT) of AED vs no AED would be feasible. METHODS: Survey of neurosurgeons/centres dealing with glioma patients in the UK regarding:(i) routine use of AED in patients with glioma(ii) preferred AED (iii) willingness to participate in a RCT of prophylactic AED(iv) were patients seen in a dedicated specialist neurosurgical clinic before surgery. A four point scale was used regarding usage of AEDs "almost always", "usually", "rarely", "almost never" to avoid centering bias. RESULTS: 71% of 35 respondents almost never prescribed AEDs while 14% almost always prescribed AEDs. 51.4% would use Levetiracetam, 11.4% phenytoin and 37.1% not applicable. 74.3% would be interested in participating in a RCT. 60% of patients were seen in a dedicated specialist neurosurgical clinic before surgery. Conclusions: Based on responses of the survey a UK RCT trial of Levetiracetam vs no AED was considered feasible and a proposal (Seizure Prophylaxis IN Glioma - SPRING) was submitted to NIHR HTA. The application was successful. SPRING will start recruiting patients over three years from Jan 2019 in 15 neurosurgical centres across the UK. ACKNOWLEDGEMENTS: National Institute of Health Research for funding, (NIHR), and UCB for supplying AED.